Recent advances of semiconducting polymer nanoparticles in in vivo molecular imaging - Pu, Kanyi; Chattopadhyay, Niladri; Rao, Jianghong (Journal of controlled release, 2016)
Semiconducting polymer nanoparticles (SPNs) emerge as attractive molecular imaging nanoagents in living animals because of their excellent optical properties including large absorption coefficients, tunable optical properties and controllable dimensions, high photostability, and the use of organic and biologically inert components without toxic metals. This review summarizes the recent advances of these new organic nanoparticles in in vivo molecular imaging. The in vivo biocompatibility of SPNs is discussed first in details, followed by examples of their applications ranging from sentinel lymph node mapping and tumor imaging to long-term cell tracking, to drug toxicity and bacterial infection imaging for fluorescence, bioluminescence, chemiluminescence and photoacoustic imaging in living animals. The utility of SPNs for designing smart activatable probes for real-time in vivo imaging is also discussed. [Display omitted]